The Effect of Competence and Teacher Professional Allowance (TPG) on the Performance of State High School Teachers in North Bengkulu (The Manager Review, 2024)
This study investigates the impact of teacher competence and professional allowances (TPG) on the performance of high school teachers in North Bengkulu. Using a survey research approach, data was collected through questionnaires distributed to a sample of teachers in the region. The collected data were then analyzed using a multiple linear regression model to assess the relationships between the variables. The findings reveal that both teacher competence and the provision of professional allowances (TPG) have a significant positive effect on teacher performance. Specifically, the study shows that increased teacher competence, as well as higher professional allowances, contribute to enhanced teacher effectiveness in the classroom. Moreover, the combined effect of both competency and professional allowances further boosts teacher performance, indicating that these factors are interconnected in improving educational outcomes. In essence, the results suggest that improving the professional qualifications of teachers and offering adequate financial incentives, such as professional allowances, can lead to noticeable improvements in teaching performance. These findings highlight the importance of supporting teachers both professionally and financially to enhance the quality of education in the region.